The inverse of the function f(x)=√x+6 will be x²-12x+36.
A function that can reverse into another function is known as an inverse function or anti-function.
The given function is,
f(x)=√x+6
As we know inverse of the function is shown as,
y = f(x)
y=√x+6
For inverse function, we have to replace the variable's place value,
x=√y+6
√y=x-6
Squaring both sides,
(√y)²=(x-6)²
y=x²+36-12x
Hence,the inverse of the function f(x)=√x+6 will be x²-12x+36.
Learn more about the Inverse function here,
https://brainly.com/question/2541698
#SPJ4